2012
DOI: 10.1186/1472-6882-12-187
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of ethanolic extract of Selaginella convoluta in mice

Abstract: BackgroundSelaginella convoluta (Arn.) Spring (Selaginellaceae), commonly known as “jericó”, is a medicinal plant found in northeastern Brazil. S. convoluta is used in folk medicine as an antidepressant, aphrodisiac, diuretic, analgesic, anti-inflammatory and it is used to combat amenorrhea, coughing and bleeding. This study was performed to evaluate the antinociceptive effects of ethanolic extract from S. convoluta in mice exposed to chemical and thermal models of nociception.MethodsPreliminary phytochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…*P < 0.05, signifi cantly different from control, analysis of variance followed Dunnett's test (n = 6, by group) to opioid analgesics, but INDO and acetylsalicylic acid respond better in the second phase. 16 The extracts showed effects in the second phase, indicating a possible anti-infl ammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“…*P < 0.05, signifi cantly different from control, analysis of variance followed Dunnett's test (n = 6, by group) to opioid analgesics, but INDO and acetylsalicylic acid respond better in the second phase. 16 The extracts showed effects in the second phase, indicating a possible anti-infl ammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, acetic acid injection induces a release of TNF-α, interleukin-1β (IL-1β) and interleukin-8(IL-8) by resident peritoneal macrophages, mast cells, prostanoids and bradykinin [28].These prostaglandin and lipoxygenase products are responsible for inflammation and pain. Substance(s) inhibiting the writhing response will have analgesic effect preferably by inhibition of prostaglandin synthesis, a peripheral mechanism of pain inhibition [30]. Non steroidal anti-inflammatory drugs (NSAIDs) can inhibit COX in peripheral tissues and therefore interfere with the mechanism of transduction of primary afferent nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Intraplantar injection of formalin has been reported to produce a distinct biphasic nociceptive response [12,21], termed first and second phases [20]. The first phase, commonly denominated early or neurogenic phase (from 0 to 5 min after injection formalin) results from a direct stimulation of nociceptors (predominantly C-fibres) [22,23,27,28,31,32,34]. Substance P, glutamate and bradykinin are thought to participate in this phase, which is believed to be non-inflammatory pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Because this model is highly sensitive and also has the ability to detect antinociceptive effects of compounds at dose levels that may appear inactive in other models [20,21]. The intraperitoneal administration of agents that irritate serous membranes provokes a stereotyped behaviour in the mice which is characterized by abdominal contractions, movements of the body as a whole and twisting of the dorso-abdominal muscles [22] and a reduction in motor activity and motor incoordination [23]. It has been suggested that acetic acid injection into peritoneal cavity leads to increased levels of cyclooxygenases (COX) and lipoxygenase [24] and indirectly leads to the release of endogenous nociceptive mediators such as PGE 2 and PGF 2α [5,20,[25][26][27][28][29][30], serotonin [22,25,26,29,30], histamine [22,26,30,31], bradykinin [21,22,24], substance P [24,25], cytokines (TNF-α, IL-1β, IL-8) [21,24,25,29] and lipoxygenase products [20], which eventually excites the primary afferent nociceptors [25] that contribute to the development of inflammatory pain [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation